EARLY GROWTH OF COMMON BEAN PLANTS IN RESPONSE TO VIGOUR SEEDS AND INOCULATION WITH Bacillus subtilis - Oliveira, G. R. F.; Silva, M. S.; Marciano, T. Y. F.; Proença, S. L.; Sá, M. E. (Revista Brasileira de Engenharia de Biossistemas, 2016)
The rhizobacteria are natural soil microorganisms showing the capability to colonize the root system of crops and benefits them through different mechanisms, which can result in promoting plant growth. Inoculation with genus Bacillus, particularly B. subtilis has been studied in many crops. In Brazil, common bean shows high socio-cultural and economic importance to the country. Growing technologies such as the use of high vigour seeds generate high-performance plants and when associated with inoculation with rhizobacteria, can benefit early crop growth, and combine productivity with agricultural sustainability. The study aimed to assess the effects of inoculation two seed lots evaluated with high and low vigour, by applying 5 doses of a product containing B. subtilis to obtain information about the effects on early growth of bean seedlings cv. BRS Estilo. The experiment was conducted in a greenhouse for 12 days and the follow agronomic parameters were evaluated: total length of seedling; primary root length; dry mass of seedlings; dry mass of the primary root. High vigour seeds associated with B. subtilis seeds promoted increments in dry matter of seedlings and dry matter of primary root.